PENGARUH PENGALAMAN AUDITOR, SKEPTISME, INTUISI, RISIKO AUDIT DAN KEAHLIAN FORENSIK TERHADAP PENDETEKSIAN KECURANGAN (FRAUD) - Juliyanti, Kania; Muslim, Ade Imam (Jurnal Riset Keuangan dan Akuntansi, 2024)
This research aims to determine the influence of auditor experience, skepticism, intuition, audit risk, and forensic expertise on fraud detection at Public Accounting Firms in Bandung City. This research is a type of quantitative research. The sampling technique was carried out using purposive sampling technique. So the samples obtained were 11 public accounting offices in Bandung City. The data collection technique used was a questionnaire distribution. The data analysis technique used in this research is multiple linear regression analysis with the SPSS 24 software tool. The results of this research show that auditor experience, skepticism, audit risk and forensic expertise influence fraud detection while intuition has no influence on fraud detection. and simultaneously the auditor's experience, skepticism, intuition, audit risk, and forensic expertise influence fraud detection.Keywords: auditor's experience, skepticism, intuition, audit risk, forensic expertise, and fraud detection.